Tinjauan Yuridis Penyesuaian Yayasan Yang Didirikan Sebelum Undang-Undang Nomor 16 Tahun 2001 - Delia Azizah Rachmapurnami (Officium Notarium, 2021)
This study examines the problems of adjusting the Articles of Association of foundations that were established prior to the issuance of the Foundation Law, the implementation of the Deed of Adjustment of Foundations by a Notary, and the legal consequences arising from the Notary's error in making the Deed of Adjustment of the Foundation's Articles of Association. This is a juridical-normative legal research method with a statutory approach and data collection through literature study with research analysis using descriptive-qualitative techniques. This study concludes, firstly, that there are still many Deeds of Adjustment to the Articles of Association of Foundations that were established before the issuance of the Foundation Law which have not been based on the Foundation Law and Government Regulation No. 2 of 2013. Second, due to the lack of understanding of the Notary in the laws and regulations, so that it is only limited to the Deed of Establishment of the New Foundation and then there are many wrong phrases related to Article 5 regarding “asset” and at the conclusion of the deed, as a result the Deed can be canceled or null and void. Third, clients can be subject to criminal sanctions and especially for Notaries can be subject to administrative sanctions, civil sanctions or criminal sanctions in accordance with applicable laws and regulationsKey Word: Adjustment, Foundation, Legal ImplicationsAbstrakPenelitian ini mengkaji problematika penyesuaian anggaran dasar yayasan yang didirikan sebelum lahirnya Undang-Undang Yayasan, implementasi Akta Penyesuaian Yayasan oleh Notaris, dan akibat hukum yang ditimbulkan atas kesalahan Notaris dalam membuat Akta Penyesuaian Anggaran Dasar Yayasan. Penelitian ini merupakan penelitian hukum yuridis-normatif dengan metode pendekatan perundang-undangan dan pengumpulan data melalui penelusuran literatur dengan analisa penelitian menggunakan teknik deskriptif-kualitatif. Penelitian ini menyimpulkan pertama, bahwa masih banyak ditemukan Akta Penyesuaian Anggaran Dasar Yayasan yang didirikan sebelum lahirnya Undang-Undang Yayasan yang belum mendasarkan pada Undang-Undang Yayasan dan Peraturan Pemerintah Nomor 2 Tahun 2013. Kedua, karena kurangnya pemahaman Notaris pada peraturan perundang-undangan, sehingga hanya sebatas dibuat Akta Pendirian Yayasan Baru dan kemudian banyak frasa-frasa yang salah terkait dengan Pasal 5 mengenai “kekayaan” dan pada penutup akta, akibatnya Akta dapat dibatalkan atau batal demi hukum. Ketiga, klien dapat dikenakan sanksi pidana dan terlebih bagi Notaris dapat dikenakan sanksi administratif, sanksi perdata ataupun sanksi pidana sesuai dengan peraturan perundang-undangan yang berlaku.Kata Kunci: Penyesuaian, Yayasan, akibat hukum